Antibody Engineering Towards Enhancement of Spike Protein SARS-COV-2 -m396 Binding Affinity - Sefid, Fateme; Payandeh, Zahra; Azamirad, Ghasem; Rasooli, Iraj (Regeneration, Reconstruction & Restoration (Triple R), 2021)
Introduction: The SARS-COV-2 is a non-segmented positive-sense RNA virus that belongs to the genus Beta Coronavirus. The envelope-anchored trimeric spike protein on the virus surface is considered to be the key protein for the viral entry into the host cells. The angiotensin-converting enzyme 2 (ACE2) is reported to be the effective human receptor for SARS-COV-2. ACE2 receptor can be prevented by neutralizing antibodies such as m396 targeting the virus receptor-binding site. Material and Methods: Considering the importance of computational docking, and in silico affinity maturation we aimed at finding the important amino acids of the m396 antibody. These amino acids were then replaced by other amino acids to improve antibody-binding affinity to receptor-binding domain (RBD) of the SARS-COV-2 spike protein. Finally, we measured the binding affinity of antibody variants to the antigen. Result: Our findings disclosed that several variant mutations could successfully improve the characteristics of the antibody binding compared to the normal antibodies. Conclusion: the antibodies developed may be possible candidates for stronger affinity binding to antigens.